2021
DOI: 10.1002/app.51239
|View full text |Cite
|
Sign up to set email alerts
|

Novel water‐soluble polymer coatings controlNPKrelease rate, improve soil quality and maize productivity

Abstract: We investigated different combinations of polymers (5% each) (i) starch, gelatin (polymer coating; PC-1), (ii) polyvinyl alcohol (PVA), gum Arabica (PC-2), (iii) PVA, gelatin (PC-3), (iv) starch, gum Arabica (PC-4), (v) gelatin, gum Arabica (PC-5), (vi) starch, PVA (PC-6), for coating NPK (17, 17:17) in a fluidized bed granulator. Morphological characterization indicated a uniform coating of all formulations on NPK granules. A slow release of N (PC-3), P (PC-6), and K (PC-3) was observed in water. In soil, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…The same method was adopted for the preparation of other compositions of coating materials. The experimental design to make a biopolymer and K combination for coating solutions was carefully thought though, based on previous reported studies [8,11,21,[36][37][38]. The coating combinations were (i) GA + KI: urea coated with 3% Gum Arabica and 5% KI, (ii) PVA + KI: urea coated with 3% Polyvinyl Alcohol and 5% KI, and (iii) Gelatin + KI: urea coated with 3% Gum Arabica and 5% KI.…”
Section: Composition Of the Coating Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same method was adopted for the preparation of other compositions of coating materials. The experimental design to make a biopolymer and K combination for coating solutions was carefully thought though, based on previous reported studies [8,11,21,[36][37][38]. The coating combinations were (i) GA + KI: urea coated with 3% Gum Arabica and 5% KI, (ii) PVA + KI: urea coated with 3% Polyvinyl Alcohol and 5% KI, and (iii) Gelatin + KI: urea coated with 3% Gum Arabica and 5% KI.…”
Section: Composition Of the Coating Solutionmentioning
confidence: 99%
“…The purpose of sampling five times was to study the mineral N, microbial biomass C, and N content of the soil with time. Each time, three soil samples (random) were collected at a standard soil sampling depth of 0-30 cm [8,[38][39][40][41] from all plots, which were mixed properly to form a composite sample. Half of each soil sample (fresh) was used for the determination of microbial biomass C and N content of soil, while the remaining half was oven dried for 2 days at a temperature of 45 • C to analyze soil pH, EC (electrical conductivity), TOC (total organic carbon), available C, N min (mineral nitrogen) and plant available P and K.…”
Section: Analysis Of Soil Samplesmentioning
confidence: 99%
“…For the NPK treatment, cultivated plants absorb small portions of nutrients during the first months and the rest are lost to the environment during the leaching process, reducing plant nutrition. 6,10 In the last measurements, the results showed that the NPK treatment proved to be the least efficient in relation to the measured parameter. It was also possible to verify that there were no significant differences between the HEDTA and PAP treatments (highlighted by "#" in Figure 4); the same was observed for HEDTA + NPK and PAP (highlighted by "*" in Figure 4) that showed the best results, and this result was directly linked to the capacity of the hydrogels retain water during the dry season.…”
Section: Physical Development Of the Seedlingsmentioning
confidence: 97%
“…With the inability to photosynthesize, aquatic plants die and their decomposition increases the biochemical oxygen demand, causing the mortality of aquatic fauna . Thus, nutrient losses to the environment cause health risks and agronomic, economic, and environmental problems. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation